THE IMPACT OF JOB TRAINING AND REWARDS ON EMPLOYEE WORK PRODUCTIVITY AT MALAHAYATI BIREUEN HOSPITAL - Fakhrurrazi, Fakhrurrazi; Irfan, Irfan; Zulfahmi, Zulfahmi (JURNAL KEBANGSAAN, 2023)
Analysis of employee work productivity, something that has become a common issue, because it is still not optimal in human resource management capacity. This analysis is related to the impact of job training and reward provision. The study was conducted on employees of Malahayati Hospital in Bireuen Regency. By taking a sample of 86 respondents. And the analysis technique with multiple regression, this quantitative study tried to answer the influence. The results found that (1) Job training and reward provision have a partial effect on employee work productivity, formulated in the equation: Y = 2.419 + 0.296 X1 + 0.429 X2. Where the reward provision factor has a higher impact than training. (2) And simultaneously also has a significant effect on increasing employee work productivity at Malahayati Hospital, with a contribution of 45.7%.